Ambiente de textualização no ensino a distância: o caso do fórum educacional - Campos, Marineide Furtado (2012)
This research deals with textualization issues present in educational forums in distance learning environment. The research aims to analyze textualization regarding communication practices between tutors and distance learning students. Specifically the research aims to verify if the educational forum is considered pertinent for knowledge construction as well as identify subject´s behavior in e-Proinfo environment. The research also aims to understand the dynamics of the teaching and learning techniques related to the forum´s printed material. This is done in order to acknowledge discourse on behalf of subjects through the presented educational assignments. In order to address the issue, the work dealt with the relations present in distance learning forums, the forms in which the assignments are made, the way social actors interact and how this debate happens in the virtual environment. The research emphasized an educational forum used in a higher education institution at Rio Grande do Norte/Brazil. Thus the research corpus is composed by messages that were posted in the forum in the module called computer material . This module is one of the last in a set of six modules that are part of The Basic Cycle for Media Training promoted by the Center for Distance Learning in a public university at Rio Grande do Norte/Brazil. The research deals with a qualitative type approach in the perspectives of Merriam (1988), Cresswell (1994) and Minayo (1996). In order to achieve this analysis, the research dealt with theoretical landmarks related to distance learning present in (Silva, 2008; Brait, 1993; Sperbe and Wilson, 1986; Marquesi and Elias 2008 as well as Xavier, 2005, amongst others. As for aspects related to media and technological perspectives present in the forum, the research dealt with (Baranov, 1989; Neuner, 1981; Kearsley and Moore, 1996). Textualization was dealt according to (Marcuschi, 2008; Costa Val, 2004) and the conceptions and functions regarding tutors was seen according to (Salgado, 2002). In the conclusion and recommendations it was seen that these discussions present relevant contributions to distance learning and go beyond the practical universe present in electronical interaction. In the final considerations it is pointed out that this research is relevant for areas such as applied linguistics and presents guidelines for those involved in continuous education and aim meaningful knowledge that is coherent with distance learning education